ADAM‐10 is overexpressed in rheumatoid arthritis synovial tissue and mediates angiogenesis. Issue 1 (27th December 2012) - Isozaki, Takeo; Rabquer, Bradley J.; Ruth, Jeffrey H.; Haines, G. Kenneth; Koch, Alisa E.
Abstract Objective To examine the expression of ADAM‐10 in rheumatoid arthritis (RA) synovial tissue (ST) and the role it plays in angiogenesis. Methods ADAM‐10 expression was determined using immunohistology, Western blotting, and quantitative polymerase chain reaction. In order to examine the role of ADAM‐10 in angiogenesis, we performed in vitro Matrigel tube formation and chemotaxis assays using human microvascular endothelial cells (HMVECs) transfected with control or ADAM‐10 small interfering RNA (siRNA). To determine whether ADAM‐10 plays a role in angiogenesis in the context of RA, we performed Matrigel assays using a coculture system of HMVECs and RA synovial fibroblasts. Results Endothelial cells and lining cells within RA ST expressed high levels of ADAM‐10 compared with cells within osteoarthritis ST and normal ST. ADAM‐10 expression was significantly elevated at the protein and messenger RNA levels in HMVECs and RA synovial fibroblasts stimulated with proinflammatory mediators compared with unstimulated cells. ADAM‐10 siRNA–treated HMVECs had decreased endothelial cell tube formation and migration compared with control siRNA–treated HMVECs. In addition, ADAM‐10 siRNA–treated HMVECs from the RA synovial fibroblast coculture system had decreased endothelial cell tube formation compared with control siRNA–treated HMVECs. Conclusion These data show that ADAM‐10 is overexpressed in RA and suggest that ADAM‐10 may play a role in RA angiogenesis. ADAM‐10 may be a potential therapeutic target in inflammatory angiogenic diseases such as RA.